1994
DOI: 10.1021/ed071p592
|View full text |Cite
|
Sign up to set email alerts
|

Improving Creativity, Solving Problems, and Communicating with Peers in Engineering and Science Laboratories

Abstract: Brining the laboratory experience into closer alignment with necessary industrial skills by emphasizing experimental selection, design, analysis, group problem-solving, and peer communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…However, there are consistent themes which constantly recur in the literature indicating that teaching methods which allow for, and encourage, peer and student-staff interaction, and the creation of a socially integrative learning environment, are most likely to enhance graduate attributes development. Key research into the student experience at university has shown that academic and social integration are critical factors in students' success at university (Evans and Peer 1999;McInnes and James 1995;Pascarella 1985;Pascarella et al 1986;Tinto 1987) which has been supported by other case studies and smaller investigations (e.g., Drake et al 1994;Jackson 2003;Mumm and Kersting 1997;Najar 2001).…”
Section: Graduate Attributes and Teaching And Learning In Higher Educmentioning
confidence: 87%
“…However, there are consistent themes which constantly recur in the literature indicating that teaching methods which allow for, and encourage, peer and student-staff interaction, and the creation of a socially integrative learning environment, are most likely to enhance graduate attributes development. Key research into the student experience at university has shown that academic and social integration are critical factors in students' success at university (Evans and Peer 1999;McInnes and James 1995;Pascarella 1985;Pascarella et al 1986;Tinto 1987) which has been supported by other case studies and smaller investigations (e.g., Drake et al 1994;Jackson 2003;Mumm and Kersting 1997;Najar 2001).…”
Section: Graduate Attributes and Teaching And Learning In Higher Educmentioning
confidence: 87%
“…At the same time, they collaborate closely with relevant and up to date ideas, innovations and insights provided by industrial partners in the preparation of college science curriculum and student projects. Feedback from partners in the local petroleum industry sets up a clear framework and vision in the correct preparation of content in science and engineering courses [43], the vital working approaches and essential critical thinking skills so necessary in the industrial work arena and in society in general [44]. Lee reported that reinforcing sound academic development and interpersonal experience in general produces healthy moral sensibilities in the study of the arts and humanities.…”
Section: Encouragementmentioning
confidence: 99%
“…Solving problems of a limited scope are certainly a part of what a chemist does, but they do not require a "flash of genius" or a leap of imagination and do not encompass the range of activities of a chemist. Working in the chemical industry, for example, it is not enough to execute and analyze an experiment, but one must also identify the most important experiment, design the experiment, select the runs, apply the results economically, and communicate the results to peers (Drake et al 1994). In this context, constructing experiments with single variables and making careful observations may be a problem-solving strategy, but not a chemist's sole activity.…”
Section: What Chemists "Do"mentioning
confidence: 99%
“…It has been argued that no meaningful learning takes place in these laboratory spaces (Tobin and Gallagher 1987) because students spend more time determining if they obtained the correct results rather than thinking about the scientific principles being applied in the laboratory, and also because these traditional laboratory activities are designed to facilitate the development of only lower-order cognitive skills such as rote learning and algorithmic problem solving. Indeed, chemical educators offering pedagogical strategies for promoting student creativity often begin by citing the deficiencies of scripted, expository instruction (Acheron and Kikuth 2005; Drake et al 1994;Buono et al 1973; Ditzler and Ricci 1994;Miller 1993;Venkatachelam and Rudolph 1974;Lipkowitz and Daniel Robertson 2000;Gallet 1988;Zielinski 2009;Scott 2010). Domin has also shown how these different laboratory instructional styles relate to Kuhn's description of the scientific enterprise (Domin 2009).…”
Section: Undergraduate Chemistry Laboratories and Creativitymentioning
confidence: 99%